Swimming turn performance: the distinguishing factor in 1500m World championship freestyle races? - Polach, M.; Thiel, D.; Kreník, J.; Born, D.-P. (BMC Research Notes, 2021)
Turn sections represent the second largest part of total race time in 1500 m freestyle races and may substantially affect race results. Therefore, the aim of the study was to investigate individual race strategies and compare the effect of start, swim, and turn performances between short-course and long-course races. Video footages were collected from all male finalists at the 2018 short- (n = 8, age 22.8 ± 2.4 years, FINA points 953 ± 27) and 2019 long-course World swimming championships (n = 8, age 23.3 ± 2.2 years, FINA points 951 ± 23) for subsequently analysis of start, turn, and swim performance.